2021
DOI: 10.7150/ijbs.60536
|View full text |Cite
|
Sign up to set email alerts
|

Mir24-2-5p suppresses the osteogenic differentiation with Gnai3 inhibition presenting a direct target via inactivating JNK-p38 MAPK signaling axis

Abstract: Background: Congenital anomalies are increasingly becoming a global pediatric health concern, which requires immediate attention to its early diagnosis, preventive strategies, and efficient treatments. Guanine nucleotide binding protein, alpha inhibiting activity polypeptide 3 (Gnai3) gene mutation has been demonstrated to cause congenital small jaw deformity, but the functions of Gnai3 in the disease-specific microRNA (miRNA) upregulations and their downstream signaling pathways during osteogenesis have not y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Activated p38MAPK already proved that it could phosphorylate and activate MAPKAPK-2 and to phosphorylate the transcription factors Max, ATF-2, and MEF2 [ 6 , 29 ]. p38 MAPK plays an important role in inflammation healing, tissue repair, embryonic development [ 30 ], immunoregulation [ 31 ], and the accommodation of cell proliferation and apoptosis [ 32 ]. Some studies reported that p38MAPK signal pathway proteins may be related to the regulation of apoptosis genes [ 33 ], or play a role in antitumor drugs activity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated p38MAPK already proved that it could phosphorylate and activate MAPKAPK-2 and to phosphorylate the transcription factors Max, ATF-2, and MEF2 [ 6 , 29 ]. p38 MAPK plays an important role in inflammation healing, tissue repair, embryonic development [ 30 ], immunoregulation [ 31 ], and the accommodation of cell proliferation and apoptosis [ 32 ]. Some studies reported that p38MAPK signal pathway proteins may be related to the regulation of apoptosis genes [ 33 ], or play a role in antitumor drugs activity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…After culture for 14 days, chondrogenic-inducing medium was added to the cell microspheres. After chondrogenic differentiation for 14 days, the outcome parameters were assessed by Alcian blue (Sigma, A5268) staining, as previously described [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, to determine the modulated effect of sitogluside with JNK and osteogenic genes, the knockdown and activation of JNK expression were applied. ShRNA (shGnai3) was thus used to downregulate the expression level of JNK, and ASM was used as an activator to increase the p-JNK level ( Meng et al, 2021 ). The alterations of osteogenic biomarkers were detected via q-PCR.…”
Section: Methodsmentioning
confidence: 99%